Persistence in Equity Fund Performance in Brazil (2014)
We examine performance persistence in the large and growing Brazilian equity fund market from 2000 to 2012. We find a significant risk-adjusted spread between a portfolio of top- and bottom-performing funds, which supports the idea that performance persists. This spread remains after controlling for market, size, distress, and momentum risk factors and tends to be larger and more significant for a set of small and retail funds. The spread is mostly driven by the underperformance of the bottom decile of funds, which is consistent with the existence of some fund managers with insufficient skills to recover investment costs. © 2014 M.E. Sharpe, Inc. All rights reserved.